THE NAMING OF MINERAL SPECIES APPROVED BY THE COMMISSION ON NEW MINERALS AND MINERAL NAMES OF THE INTERNATIONAL MINERALOGICAL ASSOCIATION: A BRIEF HISTORY - de Fourestier J. (My University, 2002)
I present an overview of the origins and the history of the CNMMN, the naming of mineral species and the IMA system of numbering those new species. Where published, the equivalence between an IMA number and a name or composition is provided. I discuss the manner in which these IMA numbers came to be published, as they were originally confidential, and many still are. I highlight the role of various individuals in creating the system for naming mineral species as it exists today.
Keywords: Commission on New Minerals and Mineral Names; CNMMN; Committee on Nomenclature and Classification of Minerals; grandfather clause; history; IMA; IMA numbers; International Mineralogical Association; nomenclature